Human genome epidemiology building the evidence for using genetic information to improve health and prevent disease - Khoury, Muin J. (New York ; Oxford : Oxford University Press, 2010)
This text describes the role that epidemiologic methods play in the continuum from gene discovery to the development and application of genetic tests. It provides a foundation that should help researchers, policy makers and practitioners integrate genomics into medical and public health practice.
Previous ed.: Oxford: Oxford University Press, 2004.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Genetic disorders -- Epidemiology; Medical genetics -- Methodology; Genomics